Stability of perovskite solar cells: issues and prospects - Chowdhury, Tanzi Ahmed; Bin Zafar, Md. Arafat; Sajjad-Ul Islam, Md; Shahinuzzaman, M; Islam, Mohammad Aminul; Khandaker, Mayeen Uddin (RSC advances, 2023)
Even though power conversion efficiency has already reached 25.8%, poor stability is one of the major challenges hindering the commercialization of perovskite solar cells (PSCs). Several initiatives, such as structural modification and fabrication techniques by numerous ways, have been employed by researchers around the world to achieve the desired level of stability. The goal of this review is to address the recent improvements in PSCs in terms of structural modification and fabrication procedures. Perovskite films are used to provide a broad range of stability and to lose up to 20% of their initial performance. A thorough comprehension of the effect of the fabrication process on the device's stability is considered to be crucial in order to provide the foundation for future attempts. We summarize several commonly used fabrication techniques - spin coating, doctor blade, sequential deposition, hybrid chemical vapor, and alternating layer-by-layer. The evolution of device structure from regular to inverted, HTL free, and ETL including the changes in material utilization from organic to inorganic, as well as the perovskite material are presented in a systematic manner. We also aimed to gain insight into the functioning stability of PSCs, as well as practical information on how to increase their operational longevity through sensible device fabrication and materials processing, to promote PSC commercialization at the end. Stability issues are the key challenges for commercialization of PSCs. Different stability issues including modification of the structural design and material, fabrication process should be considered and improved to improve the stability of PSCs.